Mouvement revivaliste et patrimoine culturel immatériel : appropriation ou évitement ? - François Gasnault (In Situ)
Associations supporting traditional music and dance took advantage of the notion of the intangible cultural heritage, as a concept and as a programme, at an early date. These associations are also often considered to be among the main promoters of the intangible cultural heritage. And indeed some of the associations which have been active both in metropolitan France and in French territories overseas, seized upon the intangible cultural heritage in the hope that the label would enhance their legitimacy and vitality. Their efforts resulted in several inscriptions on the UNESCO list. But at the same time, other actors, first of all artists within the ‘trad’ movement, went from being cautious spectators to being outright opponents. Neither consensual nor conflictual, the notion of the intangible cultural heritage seems to be renewing an old quarrel - or dialectic tension - which has existed since the beginnings of the movement, between creators and heritage actors. Some answers could be found by looking at events such as the national convention for traditional music in 2007, the controversy amongst French ethno-musicologists in 2010 and the successful application for UNESCO listing of the Breton ‘fest-noz’.